2014
DOI: 10.1148/radiol.13130733
|View full text |Cite
|
Sign up to set email alerts
|

Breast Density: Comparison of Chest CT with Mammography

Abstract: Preliminary results suggest that on further validation, breast density readings at CT may provide important additional risk information on CT of the chest and that computer-derived measurements may be helpful in such assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
(18 reference statements)
3
21
0
Order By: Relevance
“…Full paper: Semi-automated CT measure of breast density BJR inter-reader agreement of subjective CT readings was no better than that of mammographic readings, contrary to a previous study by Salvatore et al 10 Both rely on subjective assessments of breast density percentage based on a visual analysis of a threedimensional structure in two-dimensional plane. Subjective CT readings are further limited by variable positions of the breasts, and there is subjectivity of reviewers in analysing the slice with the maximum breast tissue.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Full paper: Semi-automated CT measure of breast density BJR inter-reader agreement of subjective CT readings was no better than that of mammographic readings, contrary to a previous study by Salvatore et al 10 Both rely on subjective assessments of breast density percentage based on a visual analysis of a threedimensional structure in two-dimensional plane. Subjective CT readings are further limited by variable positions of the breasts, and there is subjectivity of reviewers in analysing the slice with the maximum breast tissue.…”
Section: Discussionmentioning
confidence: 69%
“…In a post-mortem study by Johnson et al, 12 using cone beam CT (CBCT) with fuzzy c-mean algorithm and involving 40 post-mortem breasts, the authors found automatic CT measures of breast density more efficient and reduced interobserver variation. Salvatore et al 10 further evaluated a subset of 40 patients with semi-automated CT density measurement and found agreement in 90% of cases. In our study, we found our semi-automated CT density measurements agreed with subjective mammographic assessments in up to 84.4% of cases, with only one level difference in the rest.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to measure breast density from clinical standard chest CT study (27), LDCT (28, 29), cone beam CT (30), and dedicated breast CT (31, 32). Among these, LDCT is used as a clinical exam for lung cancer screening and the number of performed LDCT is increasingly rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The separation between B and the posterior muscles M P as illustrated in Figure 4 (c); (2). The separation between B and the anterior muscles M A as illustrated in Figure 4 (d).…”
Section: Separation From the Posterior Muscles M Pmentioning
confidence: 97%
“…Anterior muscles M A lying on the thoracic wall such as pectoralis major muscle and intercostal muscles; (2). Posterior muscles M P attached to scapula such as latissimus dorsi muscle and teres major muscle.…”
Section: Algorithmmentioning
confidence: 99%